2011
DOI: 10.1111/j.1365-2702.2011.03896.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and uncertainty in breast cancer survivors in Korea: differences by treatment trajectory

Abstract: To provide trajectory-sensitive nursing intervention for uncertainty among breast cancer survivors, age, marital status and pain should be considered during treatment, while factors such as economic status, dyspnoea and insomnia should be taken into account after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 34 publications
4
22
0
3
Order By: Relevance
“…Observed responses may have been influenced by how ''new'' chemotherapy was to the patient (ie, how much treatment women had already had), although previous studies have demonstrated consistently greater uncertainty levels during the treatment period compared with posttreatment. 3 n Conclusion…”
Section: Mediating Effect Of Self-efficacymentioning
confidence: 98%
See 1 more Smart Citation
“…Observed responses may have been influenced by how ''new'' chemotherapy was to the patient (ie, how much treatment women had already had), although previous studies have demonstrated consistently greater uncertainty levels during the treatment period compared with posttreatment. 3 n Conclusion…”
Section: Mediating Effect Of Self-efficacymentioning
confidence: 98%
“…1 Chemotherapy is widely used in the treatment of breast cancer and causes many adverse effects, such as hair loss, vomiting, nausea, anorexia, fatigue, anxiety, and sleep disturbance. 2,3 Women diagnosed with breast cancer are challenged to learn to manage these distressing adverse effects and also to participate in complex treatment regimens and cope with a life-threatening diagnosis. The breast cancer experience can cause significant psychological burden and put heavy self-care demands on these patients.…”
mentioning
confidence: 99%
“…Insomnia and fatigue were related to depression and depression is known to be closely associated with diminished quality of life. Broeckel and colleagues 16 , Kim, Lee and Lee 17 and Dow and colleagues 18 found that even following treatment, breast cancer survivors continued to have problems with sleep which were associated with other symptoms and adverse quality of life. Arndt and colleagues 19 reported worse quality of life and insomnia in younger colon cancer survivors when compared to the general population and in a qualitative study of 21 cancer survivors, Fleming and colleagues 13 found that the adverse effect of insomnia on quality of life lasted well beyond the cessation of active treatment for cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Research consistently indicates that greater uncertainty is associated with more symptoms of depression and anxiety and reduced quality of life in a variety of chronic illnesses [49]. Uncertainty has also been associated with worse physical symptoms (i.e., pain and fatigue) in cross sectional samples [4, 10]. Prospective research indicates that uncertainty is associated with worse shortness of breath over a two-year period among individuals with chronic obstructive pulmonary disease [6].…”
Section: Introductionmentioning
confidence: 99%